Critical factors that drive and influence consumer intentions to use m-commerce in retail stores in South Africa - Raikane, Millicent (My University, 2021)
With the growing popularity of smartphones, new opportunities in m-commerce are emerging, and these are facilitated by technological developments in internet access as well as easy access to mobile applications. However, even with these developments in technology, m-commerce adoption in South Africa is still slow. This study examined the factors that influence and/or inhibit South African consumers from adopting m-commerce, with a specific focus on the retail sector, by extending TAM. This study adopted a quantitative research methodology, and data was collected from 806 respondents through a web-based cross-sectional survey. Only 699 of the surveys were completed and therefore used for further analysis. The data was analysed by employing Factor Analysis, specifically, principal components analysis. Correlations analysis was used as an initial test of the hypotheses and thereafter, a multiple regression was run and used to accept or decline the hypotheses formally. The findings revealed that perceived usefulness, perceived ease of use, social norms, self-efficacy and trust positively and significantly affect consumers' intentions to adopt m-commerce. Perceived usefulness was found to be the most significant determinant for m-commerce adoption. Perceived risk was found to have no effect on South African consumers’ intentions to adopt m-commerce. Therefore, perceived usefulness, perceived ease of use, social norms, self-efficacy and trust are the critical factors required to drive m-commerce adoption. As retailers, marketers and developers begin to develop successful m-commerce strategies, it is important that they take into consideration these factors to ensure consumers adopt m-commerce, specifically focusing on perceived usefulness
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in the field of Digital Business, 2021
Keywords: SDG-8: Decent work and economic growth; M-commerce; M-shopping; E-commerce; Retail; Technology; Adoption; TAM; Technology Acceptance Model